Interleukin-10 downregulates Mycobacterium tuberculosis-induced Th1 responses and CTLA-4 expression. - Gong, J H (1996)
To characterize the mechanism by which interleukin 10 (IL-10) inhibits Th1 responses to intracellular pathogens, we evaluated the interaction between IL-10 and Mycobacterium tuberculosis-induced gamma interferon (IFN-gamma) production by peripheral blood mononuclear cells from persons across the spectrum of tuberculous infection. M. tuberculosis-induced IFN-gamma production was highest in healthy tuberculin reactors, intermediate in human immunodeficiency virus (HIV)-negative tuberculosis patients, and lowest in HIV-infected tuberculosis patients. Neutralizing antibodies to IL-10 increased IFN-gamma production in HIV-infected and HIV-negative tuberculosis patients by enhancing monocyte IL-12 production. Expression of the T-cell-costimulatory molecule CTLA-4 was depressed in M. tuberculosis-stimulated peripheral blood mononuclear cells from tuberculosis patients, and anti-IL-10 and Il-12 upregulated expression of CTLA-4. These findings provide evidence that intracellular pathogens can inhibit Th1 responses and downregulate expression of specific costimulatory molecules.